2004
DOI: 10.1016/s0378-1097(04)00077-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol metabolism in the extremely halophilic bacteriumSalinibacter ruber

Abstract: Growth of Salinibacter ruber, a red, extremely halophilic bacterium phylogenetically affiliated with the Flavobacterium/Cytophaga branch of the domain Bacteria, is stimulated by glycerol. In contrast to glucose consumption, which starts only after more easily degradable substrates present in yeast extract have been depleted, glycerol is consumed during the earliest growth phases. When U-14 Clabeled glycerol was added to the culture, up to 25% of the radioactivity was incorporated by the cells. Glycerol kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…3). The specific activity of glycerol kinase in parent strain H26 grown in the presence of glycerol was measured as 430 Ϯ 30 nmol ⅐ min ), and H. volcanii (31 nmol ⅐ min Ϫ1 mg Ϫ1 for cells grown in complex medium with peptides), determined in similar assays (20,23,25), this value was within a reasonable range of measurement for glycerol kinase enzymes.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…3). The specific activity of glycerol kinase in parent strain H26 grown in the presence of glycerol was measured as 430 Ϯ 30 nmol ⅐ min ), and H. volcanii (31 nmol ⅐ min Ϫ1 mg Ϫ1 for cells grown in complex medium with peptides), determined in similar assays (20,23,25), this value was within a reasonable range of measurement for glycerol kinase enzymes.…”
Section: Resultsmentioning
confidence: 62%
“…Negative control mixtures lacked ATP or glycerol, or the reactions were performed using boiled cell lysate from the parent strain H26. Samples (0.45 ml) were withdrawn at 10, 20, 30 35, 40, 45, 50, 60, and 90 min after the start of the reaction, which was terminated by the addition of 0.45 ml of 0.2 N H 3 PO 4 , and the reaction mixture was used to measure the formation of glycerol-3-phosphate with rabbit muscle glycerol-3-phosphate dehydrogenase as described previously (23).…”
mentioning
confidence: 99%
“…The above-cited microautoradiography study failed to show incorporation of glycerol into Salinibacter cells in the saltern community (Rosselló-Mora et al 2003), and the species description of Salinibacter ruber states that glycerol does not stimulate growth (Antón et al 2002). However, later studies have demonstrated that glycerol is metabolized by Salinibacter: part of the substrate is respired as CO 2 , part is incorporated into cell material (Sher et al 2004), and part is incompletely oxidized to a soluble product, which was later identified as dihydroxyacetone (Elevi Bardavid & Oren 2008b). The discrepancies between the results obtained in these different studies may well be due to the different methodologies used and the different incubation periods involved.…”
Section: Discussionmentioning
confidence: 99%
“…Cell integrity requires high salt concentrations in both cases, and growth only occurs at Ͼ2 M NaCl. Both Salinibacter and the haloarchaea are aerobic heterotrophs that exploit the large stock of organic nutrients produced in previous stages of seawater concentration, mostly by the green alga Dunaliella, and they use a similar range of organic compounds as carbon and energy sources (5). Like haloarchaea, Salinibacter contains a high proportion of carotenoids in its membrane, producing red colonies of similar appearance (2).…”
mentioning
confidence: 99%